Tungsten hexacarbonyl and hydrogen peroxide as precursors for the growth of tungsten oxide thin films on titania nanoparticles. Issue 4 (19th February 2014) - Jackson, David H. K.; Dunn, Bryan A.; Guan, Yingxin; Kuech, Thomas F.
<x xml:space="preserve">Abstract</x> W(CO)6 and H2O2 were used in an atomic layer deposition (ALD)‐like process to grow thin WOx films onto TiO2 powders in a fluidized bed reactor. Carbonyl precursors are not widely used in this application, so that deviations from an ideal ALD process, previously not examined with W(CO)6, were identified. The resulting WOx films were a result of both ALD‐like and chemical vapor deposition‐based growth modes. A chemical reaction mechanism incorporating a combination of these two growth modes was inferred. As the move to expand the range of ALD precursors meets with the desire to scale up these processes, the simultaneous appearance of both these growth modes is likely to become more and more common, and so understanding the interaction of these two types of surface reactions is key to progress in the field. The films were observed to inhibit the anatase‐to‐rutile phase transformation in the TiO2 powders upon high temperature annealing, while crystallization of the amorphous WO3 was also not observed. Changes in the local bonding within the WO3 were observed and associated with changes in the structural nature of the film and its interface to the substrate. © 2014 American Institute of Chemical Engineers AIChE J, 60: 1278–1286, 2014